On two morphologically different cysticercoids of the genus Eurycestus (Cestoda: Dilepididae) in Artemia franciscana (Arthropoda: Artemiidae) in a hypersaline pond in Dubai, United Arab Emirates - Schuster R. K. (Helminthologia, 2019)
During a survey on tapeworm larval stages in Artemia franciscana from an artificial pond in Dubai, United Arab Emirates, a high prevalence of Eurycestus avoceti-like cysticercoids was established. Adult male and female crustaceans showed a prevalence of 61.9 and 62.7 %, respectively. The intensity ranged from one to four and one to three cyst, respectively. Out of 215 examined cysticercoids, 207 specimens had morphological features matching with E. avoceti. The flaky structure of the surrounding capsule, the elongated shape of the cysticercoid and the larger number of hooklets on the suckers suggest that the eight further larval cestodes belonged to another species of the genus Eurycestus.